Identification of genes associated with resistance to disinfectants in the most common resistant bacteria strain of Bacteria isolated from Salon Tools in Ishaka Town, Bushenyi District, Uganda - Solange, Gahongayire; Namatovu, Alice; Drago Kato, Charles (IAA Journal of Biological Sciences, 2022)
This study identified the genes associated with resistance to disinfectants in the most common resistant bacteria strain of Bacteria isolated from Salon Tools in Ishaka Town, Bushenyi District, Uganda. Twenty-five (25) Salon owners/ Head operators were enrolled in this study to determine the level of awareness about the biosafety practice of salons operation using semi-structured questionnaire. Additionally, total of 125 swab samples were collected from different salons tools (combs, brushes, scissors, clippers and shaving machines) and processed using standard Microbiological methods for isolation of bacteria. The isolated bacteria were identified using standard phenotypic methods including analytical profile index (API). Quaternary ammonium compounds (qac) genes (qacA/B and C) associated with disinfectant resistances were detected from disinfectant resistant Staphylococcus aureus using Multiplex polymerase chain reaction (PCR) and Sanger sequencing methods. Results obtained from this study showed that a significant number of salon operators (p≤0.05) were aware about the important of disinfectant usage, disinfect tool(s) after use and washing hands /tools after use. Among the 125 swabbed samples collected from the salons, 78 (65.5%) were contaminated with different bacterial species. Clippers were found to have higher (25.6%) contamination among the salon tools from which samples were collected. Of all the tested disinfectants, most resistance was shown with Sodium hypochloride1%. Out of the eight (8) bacterial isolates that were analyzed for qac genes, 2(25%) isolates (STP6 and STP9) were found to be qac A/B positive while 2 (25%) isolates (STP8 and STP9) were found to be qac C gene positive. In conclusion, this study showed that, majority of the salon operators was aware about the biosafety practice of salon operation despite the higher contaminations of salons tools. qac A and qac C were detected among some S. aureus isolated. As recommendations, further study should be done and biosafety guideline should be reviewed.
Keywords: Identification; Genes; Resistance and disinfectants